Type I Interferon Induction in Cutaneous DNA Damage Syndromes - Klein, Benjamin; Günther, Claudia (Frontiers in Immunology, 2021)
Type I interferons (IFNs) as part of the innate immune system have an outstanding importance as antiviral defense cytokines that stimulate innate and adaptive immune responses. Upon sensing of pattern recognition particles (PRPs) such as nucleic acids, IFN secretion is activated and induces the expression of interferon stimulated genes (ISGs). Uncontrolled constitutive activation of the type I IFN system can lead to autoinflammation and autoimmunity, which is observed in autoimmune disorders such as systemic lupus erythematodes and in monogenic interferonopathies. They are caused by mutations in genes which are involved in sensing or metabolism of intracellular nucleic acids and DNA repair. Many authors described mechanisms of type I IFN secretion upon increased DNA damage, including the formation of micronuclei, cytosolic chromatin fragments and destabilization of DNA binding proteins. Hereditary cutaneous DNA damage syndromes, which are caused by mutations in proteins of the DNA repair, share laboratory and clinical features also seen in autoimmune disorders and interferonopathies; hence a potential role of DNA-damage-induced type I IFN secretion seems likely. Here, we aim to summarize possible mechanisms of IFN induction in cutaneous DNA damage syndromes with defects in the DNA double-strand repair and nucleotide excision repair. We review recent publications referring to Ataxia teleangiectasia, Bloom syndrome, Rothmund–Thomson syndrome, Werner syndrome, Huriez syndrome, and Xeroderma pigmentosum. Furthermore, we aim to discuss the role of type I IFN in cancer and these syndromes.